Rock art and archaeoastronomy in Morocco: preliminary observations - Ibhi,A.; Khiri, F.; Ouknine, L.; Lemjidi, A.; Asmahri El M. (Archaeoastronomy and Ancient Technologies, 2018)
The purpose of this paper is to make public the exceptional discovery in the province of Essaouira (Morocco) of three petroglyphs engraved with an original subject in Moroccan rock art. By incision, astronomical, anthropomorphic, zoomorphic figures with Tifinagh inscriptions are engraved. The distribution and the nature of the engraved subjects evoke, most probably, a testimony with a material document on a natural disaster caused most likely by the fall of a great meteorite contributing, thus; to the understanding of the Ancient History of natural disasters in Morocco.